PRMT3 reverses HIV-1 latency by increasing chromatin accessibility to form a TEAD4-P-TEFb-containing transcriptional hub - Xinyu Wang; Yuhua Xue; Lin Li; Jinwen Song; Lei Jia; Xu Li; Miao Fan; Lu Lu; Wen Su; Jingwan Han; Dandan Lin; Rongdiao Liu; et al. (Nature Communications)
Abstract Latent HIV-1 presents a formidable challenge for viral eradication. HIV-1 transcription and latency reversal require interactions between the viral promoter and host proteins. Here, we perform the dCas9-targeted locus-specific protein analysis and discover the interaction of human arginine methyltransferase 3 (PRMT3) with the HIV-1 promoter. This interaction reverses latency in cell line models and primary cells from latently infected persons by increasing the levels of H4R3Me2a and transcription factor P-TEFb at the viral promoter. PRMT3 is found to promote chromatin accessibility and transcription of HIV-1 and a small subset of host genes in regions harboring the classical recognition motif for another transcription factor TEAD4. This motif attracts TEAD4 and PRMT3 to the viral promoter to synergistically activate transcription. Physical interactions among PRMT3, P-TEFb, and TEAD4 exist, which may help form a transcriptional hub at the viral promoter. Our study reveals the potential of targeting these hub proteins to eradicate latent HIV-1.